Biological Functions of Interleukin-21 and Its Role in Inflammation - Martin Pelletier; Denis Girard (The Scientific World Journal)
Interleukin-21 (IL-21), the most recently discovered CD132-dependent cytokine, is mainly produced by activated T lymphocytes, particularly the inflammatory Th17 subset, and is believed to be a key factor in the transition between innate and acquired immunity. In the last few years, this cytokine has been shown to modulate the functions of T, B, and NK cells, as well as cells of myeloid origin. In addition, it was demonstrated that IL-21 is a potent antitumor agent, making it a promising candidate for the development of therapeutic tools. IL-21 has also been associated with different autoimmune and inflammatory diseases, such as rheumatoid arthritis and inflammatory bowel disease. This review will summarize the biological functions of IL-21 and its potential role in inflammation.